Study on Outlet Pressure of Plane Nozzle at Earth Vicinity - Naimzad, Mohammad Aref (Journal of Natural Sciences – Kabul University, 2020)
In this study, a numerical investigation was conducted on the nozzle outlet flow of vertical takeoff and landing aircraft. The flow was assumed to be steady and incompressible, and the governing equations were discretized and solved using FLUENT commercial software. The aircraft's outlet jets were modeled as both rectangular and circular cross sections. Variations in pressure, particularly dynamic pressure, from the centroid of the nozzle outlet to the ground level were plotted. The findings demonstrated good agreement with available experimental data, emphasizing that dynamic pressure decreases as the ground vicinity is approached.